Mechanical safety assessment method for transmission towers based on improved reliability theory - Zhengdao Zhou; Linfeng Zhang; Zhiyu Shang; Wang Zhang; Qianwen Wang; Zhengfa Li (Discover Applied Sciences)
Abstract Accurately assessing the safety of transmission towers is a key issue in evaluating whether the towers will function properly. For this reason, this paper combines the improved reliability theory, replaces the fuzzy uncertainty index of the tower with the consequent uncertainty index, and proposes a mechanical safety assessment method for transmission towers based on the improved reliability theory. Firstly, the indicators with attendant uncertainty in tower operating conditions were selected, and random sampling was carried out using the LHS method. Subsequently, a finite element model of the transmission tower is established, and the probability of its operating state under different operating conditions is analysed. Finally, the assessment results containing the random uncertainty of the indicators are obtained. The proposed method has been applied in the safety assessment of the Jiansu Line of ± 800 kV in Hubei, and the assessment results obtained by using this method coincide with the operational status of the actual tower. It can be considered that the method of this paper is more realistic than the traditional mechanical safety assessment methods for transmission towers.